PERANCANGAN USER INTERFACE DAN USER EXPERIENCE APLIKASI KEPEGAWAIAN BERBASIS MOBILE PADA J&T EXPRESS DENGAN METODE HUMAN CENTERED DESAIN - Puspa Mayangsari; Mohammad Badrul (LPPM Universitas Putera Batam, 2023)
Human resources are a valuable asset for every company. Human resources can help create a positive work culture, increase productivity, increase employee satisfaction, and support company growth and innovation. The J&T company is an 8-year-old shipping and logistics service company in Indonesia. Of course, employees have a lot of hope, especially in terms of welfare and transparency in the staffing system. Because this system is not yet computerized, it results in data recording errors, such as typing wrong numbers, ignoring data entry, or changing the position of numbers. Errors like this can cause inaccuracies in recorded data such as attendance, recording of overtime and others which result in recording errors in calculating employee salaries that are not appropriate. Therefore it is necessary to design a user interface and user experience to develop the application. The method used by researchers is the Human Centered Design method, which is an approach in which the system focuses on all forms of activities carried out by users and can identify what the user's needs are. This research is expected to create a solution by developing the needs of system users and creating a more modern and user friendly appearance when used by users.